Acantholachesilla gen. n. (Psocodea:’Psocoptera’: Lachesillidae: Eolachesillinae: Graphocaeciliini) from Valle del Cauca, Colombia - Aldrete, Alfonso N. García; Manchola, Oscar Fernando Saenz; Obando, Ranulfo González (Zootaxa, 2014)
Acantholachesilla saltoensis gen. et sp. n. is described from Valle del Cauca, Colombia, in the Lachesillidae, tribe Graphocaeciliini (Eolachesillinae). The genus is related to Dagualachesilla and Dagualachesilloides that occur in the same area, differing from them in the male clunial projection, phallosome, and female subgenital plate and gonapophyses.